Iron, a "miralcle cure" for chronic cardiac insufficiency? - Singler, Katrin (Zeitschrift für Gerontologie und Geriatrie, 2018)
Anemia and chronic heart failure are frequent comorbidities in geriatric patients. In approximately one third of older adults the cause of the anemia is an iron, vitamin B12 and/or folate deficiency and in another third a chronic inflammatory process is present. In the case of iron deficiency a differentiation must be made between the absolute and functional forms. Although in functional iron deficiency ferritin, as a parameter of iron metabolism, is within the normal range or can even be higher, an iron-deficient erythropoiesis is present. In cardiac insufficiency a chronic inflammatory process is assumed. According to the recent guidelines of the Deutsche Gesellschaft fur Kardiologie (DGK, German Cardiac Society) and European Society of Cardiology (ESC) a routine contol of the iron status should be performed and, if necessary, initiation of adequate supplementation is recommended.
EVALuna2:35623